(untitled) (Research, Society and Development, 2021)
This article aims to analyze the philosophy of a group of young people present in the production of confetti (concepts + affections) on the theme “violence in relation to school living”, being carried out by a researcher-group formed by 11 young people, students of 2nd and 3rd grade of high school integrated to technical courses at the State Center for Professional Education “Prefeito João Mendes Olímpio de Melo” PREMEN-NORTE, in Teresina, capital of Piauí. Sociopoetics was the methodological approach used for the investigation, once it recognizes the body, art and spirituality as a power in the collective production of knowledge. It was possible concluded from the lines of thought: Types of violence and its effects on the body of young people and the school living and The meanings of living in relation to violence, that young people highlight the violence established in the school routine with their living and personal relationships, criticizing the trivialization of the different forms of violence that has led the school to be consumed by various conflicts.